Postoperative Vision Loss after Reverse Shoulder Arthroplasty - Aadil Mumith; John Scadden (Case Reports in Orthopedics)
We report a case which highlights the rare but devastating complication of postoperative vision loss (POVL) in orthopaedic surgery. Though documented previously, it has not been reported in shoulder arthroplasty surgery of which we present the first case. The aetiology of POVL is difficult to elucidate due to its elusive nature. We explain the risks associated with regional blocks used for such surgery and how this may be related to POVL. We must be vigilant of the possible causes of POVL as curative treatment is often not possible and hence must take preventative measures which we have recommended. Fortunately, the patient fully recovered at 10 months postoperatively with excellent function of her reverse shoulder arthroplasty.